Force-Fracture Characteristics of the Roof above Goaf in a Steep Coal Seam: A Case Study of Xintie Coal Mine - Hong-sheng Tu; Shi-hao Tu; De-fu Zhu; Ding-yi Hao; Kai-jun Miao (Geofluids)
After coal is extracted from a working face in a steep coal seam (SCS), the immediate roof tends to cave in and refill the lower part of the goaf. Based on the geological conditions of a work area in a SCS and the characteristics of roof caving, this study proposed a formula for the width of the backfill in the goaf and analyzed the main factors influencing it. Based on the small-deflection theory for elastic thin plates, a working face model was created for the mechanical analysis of the main roof above a SCS before the roof fractures for the first time. Then, a roof deflection equation was derived for the estimation roof deformation under the action of both the load from overlying strata and the support provided by the backfill in the goaf. The theoretical analysis combined with the actual operational parameters at the Zuoqipian working face in #49 seam of Xintie Coal Mine shows that the maximum roof deflection is around 0.8 m and occurs at a location 39 m from the upper end of the working face. Fractures will first develop in the upper sections of the frontal and rear walls of the face and the middle of the upper suspended roof due to tension or shearing and ultimately form an E-shaped pattern. The measured support pressure and the roof deformation obtained by theoretical analysis show a similar distribution pattern, indirectly confirming the accuracy of the theoretical results.